Elastase-1 concentration in feces of term and preterm infants aged 0 - 4 months (Medical Journal of Indonesia, 2003)
Fecal elastase-1 concentration reflects exocrine pancreatic function. There have been some reports from Europe, but so far there has not been a report of fecal elastase-1 concentration in Indonesia, especially concerning infants. The aim of this study is to know the concentration of elastase-1 in feces of infants aged 1-120 days as a preliminary report of the study of the ontogeny of pancreatic elastase-1 in term and preterm infants. Fecal elastase-1 were measured from feces of 28 healthy preterm and 34 healthy term infants up to 120 days (4 month) of age. Elastase-1 concentration in infants less than 14 days of age fluctuated below 200 μg/gram feces. At the first day of life 80% preterm and 60% term infants had elastase-1 concentration less than 200 μg/gram feces, and by the age of 7 days 50% preterm and 33% term infants had elastase-1 concentration less than 200 μg/gram feces. After 14 days of age its concentration was more than 200 μg/gram feces, regardless of gestational age. This preliminary study corroborates supported the previous studies that the level of fecal elastase-1 reached normal level after 14 days. Future longitudinal study is needed to know elastase-1 concentration in infants less than 14 days. (Med J Indones 2003; 12: 69-72) Keywords: Fecal elastase-1, Infants, Enzyme-link immunosorbent assay